A method for preparing road concrete by recycling urban solid waste
In the process of preparing road concrete in urban solid waste regeneration, sodium silicate is used to modify concrete gravel, and through amino modification and crosslinking reaction technology, the mechanical properties and wear resistance of concrete are improved, solving the problem of poor performance of recycled concrete in the prior art.
Patent Information
- Application Number
- CN202510182932.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-02-19
AI Technical Summary
In the prior art, the utilization rate of urban solid waste regeneration and preparation road concrete is low, and the concrete fragments may contain impurities, resulting in poor mechanical properties of recycled concrete and insufficient wear and freezing resistance.
By stirring and drying concrete gravel, sodium silicate and deionized water in a mixer, regenerated coarse aggregate is generated; then KH-550 and ethanol are added to the mixer for amino modification to form modified regenerated coarse aggregate; combined with epoxy resin, modified curing agent, regenerated rubber powder, regenerated composite fibers and regenerated solid waste mixed powder, an interpenetrating polymer network structure is formed through cross-linking reaction, which improves the wear resistance and mechanical properties of concrete.
It improves the wear resistance, crack resistance, toughness and mechanical properties of road concrete, enhances its stability and freeze-thaw resistance in high impact environments, and extends the service life of concrete.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete processing, and in particular to a method for preparing road concrete by recycling urban solid waste. Background Art
[0002] With the accelerated development of urbanization in my country, a large amount of waste concrete is generated by the demolition of existing urban buildings. These waste concretes are directly transported to the suburbs for abandonment or simply buried, and resource utilization is extremely insufficient. According to statistics, the loss of construction materials in my country is relatively large. For every 10,000 square meters of construction, 500-600 tons of construction waste are generated. Complex composition and large quality changes are typical characteristics of construction waste. These characteristics often have a negative impact on the quality of recycled concrete, causing its strength grade to decrease. If the production activities of medium and low strength grade concrete are carried out, modern and more advanced production technologies can be used to turn waste into treasure, and the construction waste in urban development can be recycled in the concrete manufacturing process, reducing production capacity waste and promoting low-carbon sustainable development.
[0003] In the prior art, concrete fragments are often used to make concrete coarse aggregate, which is then used together with cement, fine sand, etc. to prepare road concrete. Although this method can achieve the secondary utilization of solid waste, the utilization rate is low, and the concrete fragments may contain residual cement slurry, oil stains and other impurities. These impurities will reduce the strength and bonding properties of the coarse aggregate, resulting in poor mechanical properties of the prepared recycled concrete. In order to improve the utilization rate of solid waste, the recycled coarse aggregate is mixed with recycled rubber powder, recycled composite fiber and epoxy resin materials to prepare concrete together. However, due to the poor fusion of the materials, the wear resistance, frost resistance and mechanical properties of the prepared concrete are insufficient.
[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing road concrete by recycling urban solid waste, so as to solve the technical defects proposed by the background technology.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing road concrete by recycling urban solid waste, comprising the following preparation steps:
[0008] S1. Add concrete crushed stone, sodium silicate and deionized water into a concrete mixer, stir for 30-40 minutes, and dry to obtain a crude recycled coarse aggregate;
[0009] Preparation reaction principle of recycled coarse aggregate:
[0010] During the preparation process, sodium silicate will react with concrete gravel to form silicate gel and hydraulic calcium silicate crystals, which will fill the voids and micro-cracks on the surface of concrete gravel, reduce the water absorption and crushing value of the crude recycled coarse aggregate, and improve the strength of the aggregate.
[0011] S2, adding the crude recycled coarse aggregate, KH-550 and ethanol into a concrete mixer, stirring at room temperature for 30-40 minutes, filtering and drying to obtain recycled coarse aggregate;
[0012] Preparation reaction principle of recycled coarse aggregate:
[0013] During the preparation process, the silyl ethyl of KH-550 is hydrolyzed into silanol to form a chemical bond with the crude recycled coarse aggregate, forming a coating structure on the surface of the coarse aggregate to obtain amino-modified recycled coarse aggregate.
[0014] S3, adding epoxy resin, diluent and acetone into a concrete mixer, stirring for 5-10 minutes to obtain an epoxy resin mixed solution;
[0015] Preparation reaction principle of epoxy resin mixture:
[0016] During the preparation process, adding a diluent can reduce the viscosity of the epoxy resin mixture and increase its fluidity. The epoxy resin itself can undergo a cross-linking reaction with the modified curing agent during the subsequent curing process.
[0017] S4, adding the epoxy resin mixture, ammonia solution and modified curing agent into a concrete mixer, stirring for 10-15 minutes, adding recycled rubber powder, recycled composite fiber, recycled coarse aggregate, recycled solid waste mixed powder, water reducing agent and deionized water, stirring for 5-10 minutes, and obtaining a concrete mixture;
[0018] The reaction principle for preparing concrete mixture is:
[0019] During the reaction, the amine curing agent combines with the epoxy group through a nucleophilic ring-opening reaction to form a three-dimensional cross-linked network. After the surfaces of the recycled rubber powder, composite fiber and coarse aggregate are modified by a silane coupling agent, the hydroxyl and amino groups on their surfaces can form interfacial hydrogen bonds and covalent bonds with the ether bonds and epoxy groups in the cured epoxy resin to obtain a concrete mixture.
[0020] S5. Pour the concrete mixture into a mold, place it on a vibration table, vibrate for 1-5 minutes, and post-process to obtain road concrete.
[0021] Further, in step S1, the particle size of the concrete crushed stone is 10-20 mm, and the usage ratio of the concrete crushed stone, sodium silicate and deionized water is 8-10 g: 3-5 g: 15-25 mL; in step S2, the usage ratio of the crude recycled coarse aggregate, KH-550 and ethanol is 10-12 g: 1-2 g: 110-140 mL; in step S3, the diluent is isopropyl glycidyl ether, and the usage ratio of the epoxy resin, diluent and acetone is 9-13 g: 5-6 g: 100-200 mL;
[0022] Furthermore, in step S4, the concentration of the ammonia solution is 5-10%, the recycled solid waste mixed powder is composed of slag powder, steel slag powder, and industrial secondary gypsum powder in a weight ratio of 2:2:1, the water reducer is polycarboxylic acid, and the epoxy resin mixed solution, modified curing agent, ammonia solution, recycled rubber powder, recycled composite fiber, recycled coarse aggregate, recycled solid waste mixed powder, water reducer and deionized water are used in an amount ratio of 55-60g:25-30g:10-20mL:255-260g:30-40g:350-450g:150-160g:5-8g:45-60mL; in step S5, the post-treatment includes: after the vibration is completed, placing the mold at room temperature for 24-36h, demolding, and placing the concrete block in an environment with a temperature of 20-22°C and a humidity of 80-99%RH for 28d to obtain road concrete.
[0023] Furthermore, the preparation method of the modified curing agent comprises the following steps:
[0024] A1. Place polyethylene glycol, 4,4'-diphenylmethane diisocyanate, N,N-dimethylformamide and tetrabutyltin in a reactor protected by a nitrogen atmosphere, heat to 50-60° C., and keep the temperature for reaction for 0.5-1 h to obtain a prepolymer precursor;
[0025] The preparation reaction formula of the prepolymer precursor is:
[0026]
[0027] The preparation reaction principle of the prepolymer precursor is:
[0028] Under the catalysis of tetrabutyltin, polyethylene glycol and 4,4'-diphenylmethane diisocyanate undergo nucleophilic addition to obtain a prepolymer precursor.
[0029] A2. Place the prepolymer precursor, 1,2,4-benzenetricarboxylic anhydride and N,N-dimethylformamide in a reactor protected by a nitrogen atmosphere, heat to 85-105° C., and post-treat to obtain a modified curing agent.
[0030] The preparation reaction formula of the modified curing agent is:
[0031]
[0032] Where:
[0033] The preparation reaction principle of the modified curing agent is:
[0034] During the reaction, 1,2,4-benzenetricarboxylic anhydride contains an acid anhydride with high reactivity, which undergoes nucleophilic addition under the attack of isocyanate groups to obtain a modified curing agent.
[0035] Furthermore, in step A1, the amount ratio of the polyethylene glycol, 4,4'-diphenylmethane diisocyanate, N,N-dimethylformamide and tetrabutyltin is 10-15g:8-10g:200-300mL:1g; in step A2, the amount ratio of the prepolymer precursor, 1,2,4-benzenetricarboxylic anhydride and N,N-dimethylformamide is 8-10g:4-6g:100-150mL, and the post-treatment step includes: after the reaction is completed, the reaction system is cooled to room temperature, ethyl acetate and pure water are added to the reactor, washed, and the organic phase is transferred to a rotary evaporator at a temperature of 40-50°C, and rotated until no liquid is extracted to obtain a modified curing agent.
[0036] Furthermore, the preparation method of the recycled rubber powder comprises the following steps:
[0037] B1. Put waste tire rubber powder, sodium hydroxide solution and deionized water in a reactor, heat to 50-60°C, keep warm for 1-1.5h, and post-treat to obtain crude recycled rubber powder;
[0038] The reaction principle for preparing crude recycled rubber powder is:
[0039] During the preparation process, the rubber powder is added into sodium hydroxide and deionized water and stirred, which can dissolve the hydrophobic components such as stearate remaining on the surface of the waste tire rubber powder and remove the impurities on the surface of the rubber powder.
[0040] B2. Place crude recycled rubber powder, potassium permanganate and deionized water in a reactor, heat to 50-60°C, keep warm for 1-1.5 hours, add hydrogen peroxide and urea, heat to 80-90°C, and post-treat to obtain recycled rubber powder.
[0041] The preparation reaction principle of recycled rubber powder is:
[0042] During the reaction, potassium permanganate and hydrogen peroxide oxidize the surface of the recycled tire powder, introducing hydroxyl and carboxyl groups. Urea can react with excess potassium permanganate to prevent excessive oxidation. At the same time, urea reacts with the carboxyl groups introduced by oxidation to form amides, further increasing the hydrophilicity.
[0043] Furthermore, in step B1, the concentration of the sodium hydroxide solution is 50%wt, the particle size of the waste tire rubber powder is 2-5mm, the amount ratio of the waste tire rubber powder, the sodium hydroxide solution and the deionized water is 10-12g:10-15mL:80-90mL, and the post-treatment step includes: after the reaction is completed, the reaction system is cooled to room temperature, filtered, the filter cake is washed with deionized water 1-2 times, transferred to a constant temperature drying oven, and dried to constant weight to obtain a modified rubber powder crude product; in step B2, the amount ratio of the recycled rubber powder crude product, potassium permanganate, deionized water, hydrogen peroxide and urea is 10-13g:2-4g:150-200mL:1-2mL:1-2g, and the post-treatment step includes: after the reaction is completed, after the reaction is completed, the reaction system is cooled to room temperature, filtered, the filter cake is washed with deionized water and ethanol 1-2 times, transferred to a constant temperature drying oven, and dried to constant weight to obtain recycled rubber powder.
[0044] Furthermore, the method for preparing the regenerated composite fiber comprises the following steps:
[0045] C1. Add waste glass fiber reinforced plastics and waste steel wire into a double-roll crusher for crushing, and then perform post-processing to obtain a crude regenerated composite fiber;
[0046] C2. Place the crude regenerated composite fiber, anhydrous ethanol and KH-550 in a reactor, stir at room temperature for 2-5 minutes, and perform post-treatment to obtain the regenerated composite fiber.
[0047] The preparation reaction principle of regenerated composite fiber is:
[0048] During the preparation process, the silyl ethyl of KH-550 is hydrolyzed into silanol to form a chemical bond with the crude regenerated composite fiber, forming a coating structure on the fiber surface to obtain the amino-modified regenerated composite fiber.
[0049] Furthermore, in step C1, the weight ratio of the waste glass fiber reinforced plastics to the waste steel wire is 3-4:1-1.5, and the post-processing step includes: passing the crushed crude composite fiber through a 12-mesh sieve to remove impurities, and shearing the sieved composite fiber into 9mm-10mm fibers with a shearing machine to obtain a crude regenerated composite fiber. In step C2, the amount ratio of the crude regenerated composite fiber, anhydrous ethanol and KH-550 is 5-8g:60-80mL:1-2g, and the post-processing step includes: after the reaction is completed, the reaction system is cooled to room temperature, filtered, and the filter cake is washed 1-2 times with deionized water to obtain a regenerated composite fiber.
[0050] The present invention has the following beneficial effects:
[0051] 1. A road concrete prepared by recycling urban solid waste prepared by the present invention is obtained by using epoxy resin as a cross-linking agent and a modified curing agent as a toughening agent, and mixing with recycled rubber powder, recycled coarse aggregate, recycled composite fiber, recycled solid waste mixed powder and deionized water in a concrete mixer to obtain road concrete. In the process of preparing the modified curing agent, a carboxyl-terminated curing agent is prepared by reacting isocyanate, polyethylene glycol and 1,2,4-benzenetricarboxylic anhydride. In the process of cross-linking the materials with epoxy resin, the modified curing agent and the epoxy resin form an interpenetrating polymer network structure. Due to the different solubility of the modified curing agent and the epoxy resin, when the two are cured, the molecular chain segments are entangled with each other to form an independent cross-linked network structure, and the compatibility between the two polymers is improved. When subjected to external force, stresses are transmitted to each other in the independent cross-linked network structure, so that the molecular chain segments have a certain positional offset phenomenon, and the stress can be well dispersed, thereby improving the wear resistance and mechanical properties of the road concrete.
[0052] 2. The invention prepares road concrete by recycling urban solid waste. The waste tire rubber powder is subjected to alkali washing to remove stearate and impurities on the surface of the waste tire rubber powder. Potassium permanganate, hydrogen peroxide and urea are then added to introduce hydrophilic oxygen-containing functional groups on the tire surface, thereby improving its reactivity and hydrophilicity. The recycled rubber powder, as a flexible material, can significantly improve the crack resistance and toughness of road concrete. It can absorb external impact and vibration, reduce the generation of cracks, and improve the stability of road concrete in high impact environments. After the hydrophilic groups are introduced, the particles of the recycled rubber powder have a certain water absorption capacity. In road concrete, it can absorb moisture and buffer the moisture changes inside the concrete, thereby reducing the frozen volume expansion effect of moisture in the concrete and alleviating the pressure on the internal structure of the concrete during the freeze-thaw process, thereby reducing the generation of cracks, improving the freeze-thaw resistance of road concrete, reducing the damage to road concrete caused by temperature differences, and making concrete more durable in cold areas.
[0053] 3. The present invention prepares a road concrete by recycling urban solid waste. Concrete crushed stone blocks are modified with sodium silicate. Sodium silicate reacts with recycled coarse aggregate to generate silica gel and hydraulic calcium silicate crystals to fill the surface voids and microcracks of the recycled coarse aggregate, reduce the water absorption rate and crushing value of the aggregate, thereby improving the strength of the aggregate and further improving the mechanical properties of the road concrete. The recycled coarse aggregate repaired with sodium silicate is amino-modified with a silane coupling agent to form a coating structure on the surface of the coarse aggregate, thereby improving its water resistance. The amino groups on the surface modified and the amino groups on the surface of the recycled composite fiber can form chemical bonds with a curing agent during the subsequent preparation of concrete, thereby improving the mechanical properties and wear resistance of the road concrete. Waste glass fiber reinforced plastics and waste steel wire are prepared into recycled composite fibers. The recycled composite fibers have high tensile strength and can play a reinforcing role when the road concrete is subjected to stress, thereby improving the crack resistance and toughness of the concrete. DETAILED DESCRIPTION
[0054] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] The polycarboxylic acid used in the present invention was purchased from Luoyang Tongrun Nanotechnology Co., Ltd., model 26A.
[0056] Example 1
[0057] This embodiment provides a method for preparing road concrete by recycling urban solid waste.
[0058] S1. Preparation of modified curing agent
[0059] Weigh: 100 g of polyethylene glycol, 80 g of 4,4'-diphenylmethane diisocyanate, 2 L of N,N-dimethylformamide and 10 g of tetrabutyltin, place in a reactor protected by a nitrogen atmosphere, heat to 50° C., and keep the temperature for 0.5 h to obtain a prepolymer precursor;
[0060] Weigh: 80g of prepolymer precursor, 40g of 1,2,4-tricarboxylic anhydride and 1L of N,N-dimethylformamide, place in a reactor protected by nitrogen atmosphere, heat to 85°C, after the reaction is completed, wait for the reaction system to cool to room temperature, add ethyl acetate and pure water to the reactor, wash, transfer the organic phase to a rotary evaporator at a temperature of 40°C, rotate until no liquid is extracted, and obtain a modified curing agent.
[0061] S2. Preparation of recycled rubber powder
[0062] Weigh: 100g of waste tire rubber powder, 100mL of 50%wt sodium hydroxide solution and 800mL of deionized water, put them in a reactor, heat to 50°C, and keep the temperature for 1h. After the reaction is completed, cool the reaction system to room temperature, filter, wash the filter cake with deionized water twice, transfer to a constant temperature drying oven, and dry to constant weight to obtain a modified rubber powder crude product and a recycled rubber powder crude product;
[0063] Weigh: 100 g of crude recycled rubber powder, 20 g of potassium permanganate and 1.5 L of deionized water, place them in a reactor, heat to 50°C, keep warm for 1 hour, add 10 mL of hydrogen peroxide and 10 g of urea, heat to 80°C, after the reaction is completed, wait for the reaction system to cool to room temperature, filter, wash the filter cake twice with deionized water and ethanol, transfer to a constant temperature drying oven, and dry to constant weight to obtain recycled rubber powder.
[0064] S3. Preparation of regenerated composite fibers
[0065] Weigh: 120g of waste glass fiber reinforced plastics and 40g of waste steel wire are added into a double-roll crusher for crushing, the crushed composite fiber is passed through a 12-mesh sieve to remove impurities, and the sieved composite fiber is sheared into 9mm fibers using a shearing machine to obtain a crude regenerated composite fiber;
[0066] Weigh: 50 g of crude regenerated composite fiber, 600 mL of anhydrous ethanol and 10 g of KH-550, put them into a reactor, stir at room temperature for 2 min, and after the reaction is completed, wait for the reaction system to cool to room temperature, filter, and wash the filter cake twice with deionized water to obtain regenerated composite fiber.
[0067] S4. Preparation of road concrete
[0068] Weigh: 80g of concrete crushed stone, 30g of sodium silicate and 150mL of deionized water into a concrete mixer, stir for 30min, and dry to obtain a crude recycled coarse aggregate;
[0069] Weigh: 100 g of crude recycled coarse aggregate, 10 g of KH-550 and 110-140 mL of ethanol, add into a concrete mixer, stir at room temperature for 30 min, filter, and dry to obtain recycled coarse aggregate;
[0070] Weigh: 90g of epoxy resin, 50g of diluent, and 1L of acetone, add them into a concrete mixer, and stir for 5min to obtain an epoxy resin mixed solution;
[0071] The water slag powder, steel slag powder and industrial secondary gypsum powder are mixed evenly in a weight ratio of 2:2:1 to obtain a recycled solid waste mixed powder;
[0072] Weigh: add 550 g of epoxy resin mixed liquid, 100 mL of 5% ammonia solution and 250 g of modified curing agent into a concrete mixer, stir for 10 min, add 2550 g of recycled rubber powder, 300 g of recycled composite fiber, 3500 g of recycled coarse aggregate, 1500 g of recycled solid waste mixed powder, 50 g of water reducer and 450 mL of deionized water, stir for 5 min to obtain a concrete mixture;
[0073] The concrete mixture was poured into the mold, placed on a vibration table, and vibrated for 1 minute. After the vibration was completed, the mold was placed at room temperature for 24 hours, demolded, and the concrete block was placed in an environment with a temperature of 20°C and a humidity of 80% RH for 28 days to obtain road concrete.
[0074] Example 2
[0075] This embodiment provides a method for preparing road concrete by recycling urban solid waste.
[0076] S1. Preparation of modified curing agent
[0077] Weigh: 125 g of polyethylene glycol, 90 g of 4,4'-diphenylmethane diisocyanate, 2.5 L of N,N-dimethylformamide and 10 g of tetrabutyltin, place in a reactor protected by nitrogen atmosphere, heat to 50° C., and keep the temperature for reaction for 1 hour to obtain a prepolymer precursor;
[0078] Weigh: 90g of prepolymer precursor, 50g of 1,2,4-tricarboxylic anhydride and 1.25L of N,N-dimethylformamide, place in a reactor protected by nitrogen atmosphere, heat to 90°C, after the reaction is completed, wait for the reaction system to cool to room temperature, add ethyl acetate and pure water to the reactor, wash, transfer the organic phase to a rotary evaporator at a temperature of 45°C, rotate until no liquid is extracted, and obtain a modified curing agent.
[0079] S2. Preparation of recycled rubber powder
[0080] Weigh: 110g of waste tire rubber powder, 125mL of 50%wt sodium hydroxide solution and 850mL of deionized water, put them in a reactor, heat to 55°C, and keep the temperature for 1h. After the reaction is completed, cool the reaction system to room temperature, filter, wash the filter cake with deionized water twice, transfer to a constant temperature drying oven, and dry to constant weight to obtain a modified rubber powder crude product and a recycled rubber powder crude product;
[0081] Weigh: 120g of crude recycled rubber powder, 30g of potassium permanganate and 1.7L of deionized water, place in a reactor, heat to 55°C, keep warm for 1h, add 15mL of hydrogen peroxide and 15g of urea, heat to 85°C, after the reaction is completed, wait for the reaction system to cool to room temperature, filter, wash the filter cake twice with deionized water and ethanol, transfer to a constant temperature drying oven, dry to constant weight, and obtain recycled rubber powder.
[0082] S3. Preparation of regenerated composite fibers
[0083] Weigh: 140g of waste glass fiber reinforced plastics and 50g of waste steel wire are added into a double-roll crusher for crushing, the crushed composite fiber is passed through a 12-mesh sieve to remove impurities, and the sieved composite fiber is sheared into 9mm fibers using a shearing machine to obtain a crude regenerated composite fiber;
[0084] Weigh: 70 g of crude regenerated composite fiber, 700 mL of anhydrous ethanol and 15 g of KH-550, put them into a reactor, stir at room temperature for 4 min, and after the reaction is completed, wait for the reaction system to cool to room temperature, filter, and wash the filter cake twice with deionized water to obtain regenerated composite fiber.
[0085] S4. Preparation of road concrete
[0086] Weigh: 90g of concrete crushed stone, 40g of sodium silicate and 170mL of deionized water into a concrete mixer, stir for 35min, and dry to obtain a crude recycled coarse aggregate;
[0087] Weigh: 110 g of crude recycled coarse aggregate, 15 g of KH-550 and 1.2 L of ethanol, add them into a concrete mixer, stir at room temperature for 35 min, filter and dry to obtain recycled coarse aggregate;
[0088] Weigh: 110 g of epoxy resin, 55 g of diluent, and 1.5 L of acetone, add them into a concrete mixer, and stir for 7 minutes to obtain an epoxy resin mixed solution;
[0089] The water slag powder, steel slag powder and industrial secondary gypsum powder are mixed evenly in a weight ratio of 2:2:1 to obtain a recycled solid waste mixed powder;
[0090] Weigh: add 570 g of epoxy resin mixed liquid, 150 mL of 7% ammonia solution and 270 g of modified curing agent into a concrete mixer, stir for 13 min, add 2570 g of recycled rubber powder, 350 g of recycled composite fiber, 4000 g of recycled coarse aggregate, 1500 g of recycled solid waste mixed powder, 65 g of water reducer and 500 mL of deionized water, stir for 7 min to obtain a concrete mixture;
[0091] The concrete mixture was poured into the mold, placed on a vibration table and vibrated for 3 minutes. After the vibration was completed, the mold was placed at room temperature for 30 hours, demolded, and the concrete block was placed in an environment with a temperature of 21°C and a humidity of 85%RH for 28 days to obtain road concrete.
[0092] Example 3
[0093] This embodiment provides a method for preparing road concrete by recycling urban solid waste.
[0094] S1. Preparation of modified curing agent
[0095] Weigh: 150 g of polyethylene glycol, 100 g of 4,4'-diphenylmethane diisocyanate, 3 L of N,N-dimethylformamide and 10 g of tetrabutyltin, place in a reactor protected by a nitrogen atmosphere, heat to 60° C., and keep the temperature for 1 hour to obtain a prepolymer precursor;
[0096] Weigh: 100 g of prepolymer precursor, 60 g of 1,2,4-tricarboxylic anhydride and 1.5 L of N,N-dimethylformamide, place in a reactor protected by nitrogen atmosphere, heat to 105°C, after the reaction is completed, wait for the reaction system to cool to room temperature, add ethyl acetate and pure water to the reactor, wash, transfer the organic phase to a rotary evaporator at a temperature of 50°C, rotate until no liquid is extracted, and obtain a modified curing agent.
[0097] S2. Preparation of recycled rubber powder
[0098] Weigh: 120g of waste tire rubber powder, 150mL of 50%wt sodium hydroxide solution and 900mL of deionized water are placed in a reactor, heated to 60°C, and kept warm for 1.5h. After the reaction is completed, the reaction system is cooled to room temperature, filtered, and the filter cake is washed twice with deionized water, transferred to a constant temperature drying oven, and dried to constant weight to obtain a modified rubber powder crude product and a recycled rubber powder crude product;
[0099] Weigh: 130 g of crude recycled rubber powder, 40 g of potassium permanganate and 2 L of deionized water, place them in a reactor, heat to 60°C, keep warm for 1.5 hours, add 20 mL of hydrogen peroxide and 20 g of urea, heat to 90°C, after the reaction is completed, wait for the reaction system to cool to room temperature, filter, wash the filter cake twice with deionized water and ethanol, transfer to a constant temperature drying oven, and dry to constant weight to obtain recycled rubber powder.
[0100] S3. Preparation of regenerated composite fibers
[0101] Weigh: 160g of waste glass fiber reinforced plastics and 60g of waste steel wire are added into a double-roll crusher for crushing, the crushed composite fiber is passed through a 12-mesh sieve to remove impurities, and the sieved composite fiber is sheared into 10mm fibers using a shearing machine to obtain a crude regenerated composite fiber;
[0102] Weigh: 80 g of crude regenerated composite fiber, 800 mL of anhydrous ethanol and 20 g of KH-550, put them into a reactor, stir at room temperature for 5 min, and after the reaction is completed, wait for the reaction system to cool to room temperature, filter, and wash the filter cake twice with deionized water to obtain regenerated composite fiber.
[0103] S4. Preparation of road concrete
[0104] Weigh: 100 g of concrete crushed stone, 50 g of sodium silicate and 200 mL of deionized water, add them into a concrete mixer, stir for 40 min, and dry to obtain a crude recycled coarse aggregate;
[0105] Weigh: 120 g of crude recycled coarse aggregate, 20 g of KH-550 and 1.4 L of ethanol, add into a concrete mixer, stir at room temperature for 40 min, filter, and dry to obtain recycled coarse aggregate;
[0106] Weigh: 130 g of epoxy resin, 60 g of diluent, and 2 L of acetone, add into a concrete mixer, stir for 10 min, and obtain an epoxy resin mixed solution;
[0107] The water slag powder, steel slag powder and industrial secondary gypsum powder are mixed evenly in a weight ratio of 2:2:1 to obtain a recycled solid waste mixed powder;
[0108] Weigh: add 600 g of epoxy resin mixed liquid, 200 mL of 10% ammonia solution and 300 g of modified curing agent into a concrete mixer, stir for 15 min, add 2600 g of recycled rubber powder, 400 g of recycled composite fiber, 4500 g of recycled coarse aggregate, 1600 g of recycled solid waste mixed powder, 80 g of water reducing agent and 600 mL of deionized water, stir for 10 min to obtain a concrete mixture;
[0109] The concrete mixture was poured into the mold, placed on a vibration table, and vibrated for 5 minutes. After the vibration was completed, the mold was placed at room temperature for 36 hours, demolded, and the concrete block was placed in an environment with a temperature of 22°C and a humidity of 90%RH for 28 days to obtain road concrete.
[0110] Comparative Example 1
[0111] The difference between this comparative example and Example 3 is that step S1 is eliminated, and in step S4, an equal amount of diethylenetriamine is used to replace the modified curing agent.
[0112] Comparative Example 2
[0113] The difference between this comparative example and Example 3 is that step S2 is eliminated, and in step S4, an equal amount of waste tire rubber powder is used to replace the recycled rubber powder.
[0114] Comparative Example 3
[0115] The difference between this comparative example and Example 3 is that step S3 is eliminated, and in step S4, an equal amount of crude regenerated composite fiber is used to replace the regenerated composite fiber.
[0116] Performance Test:
[0117] The flexural strength, compressive strength, splitting tensile strength, bonding strength, wear resistance and water absorption of the road concrete prepared in Examples 1-3 and Comparative Examples 1-3 after solidification for 28 days were tested with reference to the standard GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete";
[0118] With reference to the standard GB / T 50082-2024 "Standard for Test Methods for Long-term Performance and Durability of Concrete", the frost resistance of the road concrete prepared in Examples 1-3 and Comparative Examples 1-3 was tested after solidification for 28 days. The specific data are shown in Table 1.
[0119] Table 1. Performance test table of each sample
[0120] Project Group Group Group Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Flexural strength / MPa 10.3 13.5 12.5 8.6 9.1 8.5 Compressive strength / MPa 69.3 71.2 69.8 60.1 61.8 62.4 Splitting tensile strength / MPa 5.3 6.9 6.4 4.7 4.9 4.4 Bond strength / MPa 1.2 1.4 1.2 0.5 0.6 0.7 <![CDATA[Wear amount after 45 cycles / kg·m 2 > 1.89 1.45 2.27 3.14 3.12 3.16 Strength loss rate after 300 cycles of slow freezing / % 16.9 15.5 16.1 22.6 22.3 21.8
[0121] Data Analysis:
[0122] Comparing and analyzing the data in Table 1 above, the road concrete prepared by urban solid waste recycling prepared by the present invention has a flexural strength of 13.5 MPa, a compressive strength of 71.2 MPa, a splitting tensile strength of 6.9 MPa, a bonding strength of 1.4 MPa, and an abrasion loss of 1.45 kg·m after 45 cycles. 2 The strength loss rate after 300 cycles of slow freezing is 15.5%, and all performance parameters are better than those of the comparative example, indicating that the present invention is a process of preparing a modified curing agent, in which a carboxyl-terminated curing agent is prepared by reacting isocyanate, polyethylene glycol and 1,2,4-benzenetricarboxylic anhydride, and the modified curing agent and the epoxy resin form an interpenetrating polymer network structure. When the two are cured, the molecular segments are entangled with each other to form an independent cross-linked network structure, and the compatibility between the two polymers is improved. When subjected to external force, the stress will be transmitted to each other in the independent cross-linked network structure, causing a certain positional offset phenomenon of the molecular segments, and the stress can be better dispersed, thereby improving the road concrete. The wear resistance and mechanical properties of concrete are improved; the waste tire rubber powder is alkaline washed to remove the stearate and impurities on the surface of the waste tire rubber powder, and then potassium permanganate, hydrogen peroxide and urea are added to introduce hydrophilic oxygen-containing functional groups on the tire surface, which improves its reactivity and hydrophilicity. As a flexible material, the recycled rubber powder can significantly improve the crack resistance and toughness of road concrete; the concrete gravel is modified with sodium silicate, and the sodium silicate reacts with the recycled coarse aggregate to form silica gel and hydraulic calcium silicate crystals, which fill the voids and microcracks on the surface of the recycled coarse aggregate, reduce the water absorption rate and crushing value of the aggregate, thereby increasing the aggregate strength and further improving the mechanical properties of road concrete.
[0123] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing road concrete by recycling urban solid waste, characterized in that: The method comprises the following preparation steps: S1. Add concrete crushed stone, sodium silicate and deionized water into a concrete mixer, stir for 30-40 minutes, and dry to obtain a crude recycled coarse aggregate; S2, adding the crude recycled coarse aggregate, KH-550 and ethanol into a concrete mixer, stirring at room temperature for 30-40 minutes, filtering and drying to obtain recycled coarse aggregate; S3, adding epoxy resin, diluent and acetone into a concrete mixer, stirring for 5-10 minutes to obtain an epoxy resin mixed solution; S4, adding the epoxy resin mixture, ammonia solution and modified curing agent into a concrete mixer, stirring for 10-15 minutes, adding recycled rubber powder, recycled composite fiber, recycled coarse aggregate, recycled solid waste mixed powder, water reducing agent and deionized water, stirring for 5-10 minutes, and obtaining a concrete mixture; S5, pouring the concrete mixture into a mold, placing it on a vibration table, vibrating it for 1-5 minutes, and post-processing to obtain road concrete; Wherein, the preparation method of the modified curing agent comprises the following steps: A1. Place polyethylene glycol, 4,4'-diphenylmethane diisocyanate, N,N-dimethylformamide and tetrabutyltin in a reactor protected by a nitrogen atmosphere, heat to 50-60° C., and keep the temperature for reaction for 0.5-1 h to obtain a prepolymer precursor; A2. Place the prepolymer precursor, 1,2,4-benzenetricarboxylic anhydride and N,N-dimethylformamide in a reactor protected by a nitrogen atmosphere, heat to 85-105° C., and post-treat to obtain a modified curing agent.
2. The method for preparing road concrete by recycling urban solid waste according to claim 1, characterized in that: In step S1, the particle size of the concrete crushed stone is 10-20 mm, and the amount ratio of the concrete crushed stone, sodium silicate and deionized water is 8-10 g: 3-5 g: 15-20 mL; in step S2, the amount ratio of the crude recycled coarse aggregate, KH-550 and ethanol is 10-12 g: 1-2 g: 110-140 mL; in step S3, the diluent is isopropyl glycidyl ether, and the amount ratio of the epoxy resin, diluent and acetone is 9-13 g: 5-6 g: 100-200 mL; in step S4, the ammonia solution is The concentration of the liquid is 5-10%, the recycled solid waste mixed powder is composed of water slag powder, steel slag powder, and industrial secondary gypsum powder in a weight ratio of 2:2:1, the water reducer is polycarboxylic acid, and the epoxy resin mixed liquid, modified curing agent, ammonia solution, recycled rubber powder, recycled composite fiber, recycled coarse aggregate, recycled solid waste mixed powder, water reducer and deionized water are used in a ratio of 55-60g:25-30g:10-20mL:255-260g:30-40g:350-450g:150-160g:5-8g:45-60mL.
3. The method for preparing road concrete by recycling urban solid waste according to claim 1, characterized in that: In step A1, the amount ratio of the polyethylene glycol, 4,4'-diphenylmethane diisocyanate, N,N-dimethylformamide and tetrabutyltin is 10-15g:8-10g:200-300mL:1g; in step A2, the amount ratio of the prepolymer precursor, 1,2,4-benzenetricarboxylic anhydride and N,N-dimethylformamide is 8-10g:4-6g:100-150mL.
4. The method for preparing road concrete by recycling urban solid waste according to claim 1, characterized in that: The preparation method of recycled rubber powder comprises the following steps: B1. Put waste tire rubber powder, sodium hydroxide solution and deionized water in a reactor, heat to 50-60°C, keep warm for 1-1.5h, and post-treat to obtain crude recycled rubber powder; B2. Place crude recycled rubber powder, potassium permanganate and deionized water in a reactor, heat to 50-60°C, keep warm for 1-1.5 hours, add hydrogen peroxide and urea, heat to 80-90°C, and post-treat to obtain recycled rubber powder.
5. The method for preparing road concrete by recycling urban solid waste according to claim 4, characterized in that: In step B1, the concentration of the sodium hydroxide solution is 50wt%, the particle size of the waste tire rubber powder is 2-5mm, and the usage ratio of the waste tire rubber powder, the sodium hydroxide solution and the deionized water is 10-12g:10-15mL:80-90mL; in step B2, the usage ratio of the crude recycled rubber powder, potassium permanganate, deionized water, hydrogen peroxide and urea is 10-13g:2-4g:150-200mL:1-2mL:1-2g.
6. The method for preparing road concrete by recycling urban solid waste according to claim 1, characterized in that: The method for preparing the regenerated composite fiber comprises the following steps: C1. Add waste glass fiber reinforced plastics and waste steel wire into a double-roll crusher for crushing, and then perform post-processing to obtain a crude regenerated composite fiber; C2. Place the crude regenerated composite fiber, anhydrous ethanol and KH-550 in a reactor, stir at room temperature for 2-5 minutes, and perform post-treatment to obtain the regenerated composite fiber.
7. The method for preparing road concrete by recycling urban solid waste according to claim 6, characterized in that: In step C1, the weight ratio of the waste glass fiber reinforced plastics to the waste steel wire is 3-4:1-1.5; in step C2, the usage ratio of the crude regenerated composite fiber, anhydrous ethanol and KH-550 is 5-8g:60-80mL:1-2g.
Citation Information
Patent Citations
Fluorine and silicon-containing polyurethane prepolymer-modified epoxy resin and preparation method thereof
CN106750106A
Cementing material for rapid first-aid repair and rush-building, pavement material and construction method for first-aid repair and rush-building of pavement
CN117327375A